2017
DOI: 10.1097/meg.0000000000000801
|View full text |Cite
|
Sign up to set email alerts
|

Granulocyte colony-stimulating factor improves survival of patients with decompensated cirrhosis: a randomized-controlled trial

Abstract: GCSF therapy improves survival and clinical outcome in patients with decompensated cirrhosis. It may be useful in patients awaiting transplantation to prevent worsening during the waiting period. Further studies are needed to explore whether repeated periodic GCSF courses can further increase the survival and decrease the need for liver transplantation.Clinical trial registered at https://clinicaltrials.gov vide NCT02642003.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
44
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(44 citation statements)
references
References 29 publications
0
44
0
Order By: Relevance
“…Prajapati et al 56 conducted the largest randomized controlled study of GCSF therapy, using 253 decompensated cirrhosis patients. The authors showed that the cumulative survival was significantly higher in GCSF-treated patients compared to controls (79 vs. 68%) and that significantly more patients in the GCSF group had an improvement in CTP scores at 180 days.…”
Section: Critical Appraisal Of Gcsf In Decompensated Cirrhosismentioning
confidence: 99%
See 1 more Smart Citation
“…Prajapati et al 56 conducted the largest randomized controlled study of GCSF therapy, using 253 decompensated cirrhosis patients. The authors showed that the cumulative survival was significantly higher in GCSF-treated patients compared to controls (79 vs. 68%) and that significantly more patients in the GCSF group had an improvement in CTP scores at 180 days.…”
Section: Critical Appraisal Of Gcsf In Decompensated Cirrhosismentioning
confidence: 99%
“…Even though those authors stated that the inclusion of only decompensated cirrhosis as one of the strengths of their study, the table detailing patient characteristics shows the inclusion of acute-on-chronic liver failure (ACLF) patients also. ACLF patients have completely different disease mechanisms, progression, clinical outcome and possibly, distinct response to GCSF therapy in comparison to patients with decompensated cirrhosis, and hence the study by Prajapati and colleagues 56 does not fully realize the potential of GCSF use in decompensated cirrhosis. The authors do not discuss MELD progression in their study among GCSF-treated patients even though baseline values for the same are mentioned and the study is restricted to an intermediate follow up period.…”
Section: Critical Appraisal Of Gcsf In Decompensated Cirrhosismentioning
confidence: 99%
“…[10][11] G-CSF has shown to improve short-term survival and clinical outcomes in Alcoholic Hepatitis 12 , ACLF 13 and Decompensated CLD. 14 Immune paralysis leads to sepsis and hence Hepato-Renal Syndrome (HRS) and Hepatic Encephalopathy (HE) in patients with cirrhosis. 15 G-CSF has been shown to improve immune function in patients of liver disease.…”
Section: Introductionmentioning
confidence: 99%
“…GCSF therapy also improves both the chances of survival and the clinical outcome in patients with decompensated cirrhosis. 14 Hence, in this pilot study we tried to see if there is any benefit of GCSF in overall chronic liver disease patients, in terms of mortality within one month of hospital admission and improvement in CTP and MELD scores, irrespective of their stage and presentation…”
Section: Introductionmentioning
confidence: 99%
“…( 22,23 ) Clinical trials treating patients with compensated and decompensated cirrhosis with G‐CSF demonstrate contradictory results. ( 23‐27 )…”
mentioning
confidence: 99%